Pengaruh Ukuran dan Warna Kerabang Telur Itik Terhadap Hasil Pengasinan - Purba, Rio Edy Saputra; Tamrin, Tamrin; Rahmawati, Winda; Warji, Warji (Jurnal Agricultural Biosystem Engineering, 2025)
This study aims to study the effect of shell color and duck egg size on salting results. The method used in this study is a factorial Completely Randomized Design (CRD) with 3 treatment levels and 3 replications. The first factor is egg size and the second factor is duck egg shell color. The parameters observed were thickness, weight changes, texture, NaCl, and organoleptics such as aroma, color, texture, saltiness and preference. Data from the observation results will be analyzed using analysis of variance (ANOVA) followed by the HSN (Honest Significant Difference) test if there is a significant effect. The results showed that the treatment of duck egg shell size had a significant effect (Fhit>Ftab) on the thickness of texture, NaCl, aroma organoleptic and texture of mash. Then the interaction of treatments had a significant effect (Fhit>Ftab) on organoleptic mash. While the color treatment did not have a significant effect (Fhit<Ftab) on all parameters. The conclusion obtained in this study is that the larger the egg size, the higher the thickness, texture, organoleptic aroma and flavor values of salted duck eggs, while the NaCl content is lower.